Pendekatan Command Control dalam Implementasi Kebijakan Pencegahan dan Penanganan Stunting di Desa Serdang Kulon Kecamatan Panongan Kabupaten Tangerang - 'Inayah, Awaliyyatul; Arif Kurniawan, Irvan; Yusuf, Yusmedi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research discusses the command control approach in implementing stunting prevention and handling policies. It aims to describe the implementation of stunting prevention and handling in Serdang Kulon Village, Panongan Sub-district, Tangerang Regency. Although the decline in stunting rates is quite good, several problems have still been found. To see the implementation with a command control approach, Van Metter and Van Horn's theory was chosen because external environment indicators are considered relevant to the problems that exist in the implementation process. The research used a descriptive qualitative approach. The results showed that implementing stunting prevention and handling policies in Serdang Kulon Village was optimal. The factors that are still not optimal are related to external conditions and to the disposition or attitude of implementors regarding responses related to obstacles that arise in the policy implementation process.